Comparative Study Between Native and Modified Starches Isolated from Tamarind Seed - Tripathi Shalvika; Akansha; Shaida Bushra (BIO Web of Conferences)
Starch is a complex carbohydrate polymer produced by plants and especially by crops in huge amounts. It consists of amylose and amylopectin which have α-1,4- and α-1,6-linked glucose units. Seeds represent a potential source of starch, containing at least 60–70% of total starch, however many of them are treated as waste and are usually discarded. Tamarind seeds known to be high in Xyloglycan. The tamarind pulp industry underutilised byproduct, the seeds, has been proposed as a low-cost source of raw materials for industrial uses. The objective of the present work was to perform comparative study between native starch and modified starch depending upon their morphological, functional and rheological properties. One part of starch was modified by ultrasonication, the other part was the counterpart and termed as native starch. The key findings was proximate composition analysis revealed a decrease in moisture content from 12.5% for native starch to 9.9% after 20 minutes of sonication, whereas ash, protein, and lipid contents slightly increased, possibly due to the structural changes in the starch matrix, morphological analysis showed an increase in surface roughness, which in turn provides greater potential for enzymatic interactions and functional properties of the starches ranges from (75 to 90±1.12%)water absorption capacity, (0.26% to 0.85%) Bulk density,(0.84% to 2.49%) oil absorption capacity, (6.12% to 8.61%)swelling capacity and (6.34±0.05 to 6.56±0.02%) ph. Significant differences were observed from the functional properties of the starches due to modification. These results indicate that sonicated TSS is a robust and environmentally friendly biopolymer with potential uses in the food science and pharmaceutical industry and other industries where new material solutions are required.